Multisensory Impact of Sport Events A Comparative Effect Analysis Based on Soccer Games - Tham, Thorsten (Schriftenreihe der HHL Leipzig Graduate School of Management, 2016)
Thorsten Tham highlights the fundamental changes that have swept Germany's footballing landscape in recent years and presents theory-based impact hypotheses about forms of stimulus that can raise the loyalty of football-affine target groups before, during and after the game. Based on the example of traditional club VfL Bochum 1848 an online survey to analyze the influence of a Bundesliga match on different visitor target groups is conducted. The author discusses ways in which football clubs can change their multisensual approach to raise the profile of their club brand among football-affine target groups and increase loyalty to the club. Contents .Brand Management in Sports ·Consideration of Multisensuality in S-O-R Models .Empirical Study of Sensual Perception and Effectiveness During Games of the German Soccer Club Vfl Bochum 1848 ·Derivations of Potential Actions in the Context of Identity-Based Brand Management Target Groups ·Researchers and students in the fields of sports marketing and management ·Practitioners in these areas The Author Dr. Thorsten Tham completed his doctoral study under the supervision of Prof. Dr. Manfred Kirchgeorg at the SVI-Endowed Chair of Marketing at HHL Leipzig Graduate School of Management. .